Monitoring Rural Water Points in Tanzania with Mobile Phones : The Evolution of the SEMA App - Lemmens, R.L.G. (2020)
Development professionals have deployed several mobile phone-based ICT (Information and Communications Technology) platforms in the global South for improving water, health, and education services. In this paper, we focus on a mobile phone-based ICT platform for water services, called Sensors, Empowerment and Accountability in Tanzania (SEMA), developed by our team in the context of an action research project in Tanzania. Water users in villages and district water engineers in local governments may use it to monitor the functionality status of rural water points in the country. We describe the current architecture of the platform’s front-end (the SEMA app) and back-end and elaborate on its deployment in four districts in Tanzania. To conceptualize the evolution of the SEMA app, we use three concepts: transaction-intensiveness, discretion and crowdsourcing. The SEMA app effectively digitized only transaction-intensive tasks in the information flow between water users in villages and district water engineers. Further, it resolved two tensions over time: the tension over what to report (by decreasing the discretion of reporters) and over who should report (by constraining the reporting “crowd”).